Spatial and Temporal Variability of Iodine in Aerosol - Gómez Martín, Juan Carlos (2021)
In this work, we describe the compilation and homogenization of an extensive data set of aerosol iodine field observations in the period between 1963 and 2018 and we discuss its spatial and temporal dependences by comparison with CAM-Chem model simulations. A close to linear relationship between soluble and total iodine in aerosol is found (∼80% aerosol iodine is soluble), which enables converting a large subset of measurements of soluble iodine into total iodine. The resulting data set shows a distinct latitudinal dependence, with an enhancement toward the Northern Hemisphere (NH) tropics and lower values toward the poles. This behavior, which has been predicted by atmospheric models to depend on the global distribution of the main oceanic iodine source (which in turn depends on the reaction of ozone with aqueous iodide on the sea water-air interface, generating gas-phase I2 and HOI), is confirmed here by field observations for the first time. Longitudinally, there is some indication of a wave-one profile in the tropics, which peaks in the Atlantic and shows a minimum in the Pacific. New data from Antarctica show that the south polar seasonal variation of iodine in aerosol mirrors that observed previously in the Arctic, with two equinoctial maxima and the dominant maximum occurring in spring. While no clear seasonal variability is observed in NH middle latitudes, there is an indication of different seasonal cycles in the NH tropical Atlantic and Pacific. Long-term trends cannot be unambiguously established as a result of inhomogeneous time and spatial coverage and analytical methods.